Kidney Function Tests in Children with Beta-Thalassemia Minor in Zahedan, Southeast of Iran (Iranian Journal of Kidney Diseases, 2011)
There is little information regarding kidney function in patients with beta-thalassemia minor. In this study we investigated kidney function tests in 50 children with beta-thalassemia minor (22 boys and 28 girls). Twenty-four-hour urine samples were collected and analyzed for sodium, potassium, calcium, magnesium, creatinine, phosphate, uric acid, protein, and beta2-microglobulin. Blood samples were obtained for hematologic and biochemical analyses including complete blood count, serum ferritin, sodium, potassium, calcium, phosphate, magnesium, creatinine, and uric acid. This group of children with beta-thalassemia showed some evidence of tubulopathy such as proteinuria (32%), beta2-microglobulin excretion (36%), calciuria (4%), phosphaturia (4%), and uricosuria (20%). Our findings support the existence of renal tubular dysfunction in beta-thalassemia minor. However, further studies in large series are needed to shed light on the possible relation of these two distinct diseases.